More Is Better: Selecting for Broad Host Range Bacteriophages - Ross, Alexa; Ward, Samantha; Hyman, Paul (Frontiers in Microbiology, 2016)
Bacteriophages are viruses that infect bacteria. In this perspective, we discuss several aspects of a characteristic feature of bacteriophages, their host range. Each phage has its own particular host range, the range of bacteria that it can infect. While some phages can only infect one or a few bacterial strains, other phages can infect many species or even bacteria from different genera. Different methods for determining host range may give different results, reflecting the multiple mechanisms bacteria have to resist phage infection and reflecting the different steps of infection each method depends on. This makes defining host range difficult. Another difficulty in describing host range arises from the inconsistent use of the words “narrow” and especially “broad” when describing the breadth of the host range. Nearly all bacteriophages have been isolated using a single host strain of bacteria. While this procedure is fairly standard, it may more likely produce narrow rather than broad host range phage. Our results and those of others suggest that using multiple host strains during isolation can more reliably produce broader host range phages. This challenges the common belief that most bacteriophages have a narrow host range. We highlight the implications of this for several areas that are affected by host range including horizontal gene transfer and phage therapy.